POLICY ANALYSIS STUDY OF THE TRAFFIC ACCIDENT OF CRIMINAL SYSTEM WHICH MAKE LOSS OF LIFE - Ong Argo Victoria; Ade Riusma Ariyana (UNISSULA, 2020)
There were many cases of traffic accidents area during 2019. These cases were dominated by elements of neglect which resulted in the loss of a person's life. This study aims to determine formal legal considerations in passing decisions on traffic crimes resulting in the loss of a person's life resulting in the death of another person and to analyze the policy on the traffic accident criminal system that results in the loss of a person's life. The research method used is the Normative Juridical Method based on facts, document studies, field surveys and interviews, then analyzed to get a conclusion. The result of this research are the Public Prosecutor uses a single indictment, the indictment prepared by the Public Prosecutor has met the formal and material requirements. And Legal considerations of the Panel of Judges in imposing criminal sanctions against the defendant, the defendant is sentenced to imprisonment for 1 year because he is proven guilty of a criminal act because his negligence caused the death of a person.